Heat shock alters nuclear ribonucleoprotein assembly in Drosophila cells. - Mayrand, S (1983)
Heterogeneous nuclear RNA is normally complexed with a specific set of proteins, forming ribonucleoprotein particles termed hnRNP. These particles are likely to be involved in mRNA processing. We have found that the structure of hnRNP is profoundly altered during the heat shock response in Drosophila cultured cells. Although hnRNA continues to be synthesized at a near-normal rate during heat shock, its assembly into hnRNP is incomplete, as evidenced by a greatly decreased protein content of the particles in Cs2SO4 density gradients. RNA-protein cross-linking conducted in vivo (Mayrand and Pederson, Proc. Natl. Acad. Sci. U.S.A. 78:2208-2212, 1981) also reveals that hnRNA made during heat shock is complexed with greatly reduced amounts of protein. The block of hnRNP assembly occurs immediately upon heat shock, even before the onset of heat shock protein synthesis. Additional experiments reveal that hnRNP assembled normally at 25 degrees C subsequently disassembles during heat shock. The capacity for normal hnRNP assembly is gradually restored after heat-shocked cells are returned to 25 degrees C. Heat-shocked mammalian cells also show a similar block in hnRNP assembly. We suggest that incomplete assembly of hnRNP during heat shock leads to abortive processing of most mRNA precursors and favors the processing or export (or both) of others whose pathway of nuclear maturation is less dependent on, or even independent of, normal hnRNP particle structure. This hypothesis is compatible with a large number of previous observations.